Passive Real-world Interface Props for Neurosurgical - Goble, John C.; Hinckley, Ken; Kassell, Neal F.; Pausch, Randy (Association for Computing Machinery, Inc., 1994)
We claim that physical manipulation of familiar real-world objects in the user`s real environment is an important technique for the design of three-dimensional user interfaces. Thesereal-world passive interface props are manipulated by the user to specify spatial relationships between interface objects. By unobtrusively embedding free-space position and orientation trackers within the props, we enable the computer to passively observe a natural user dialog in the real world, rather than forcing the user to engage in a contrived dialog in the computer-generated world. We present neurosurgical planning as a driving application and demonstrate the utility of a head viewing prop, a cutting-plane selection prop, and a trajectory selection prop in this domain. Using passive props in this interface exploits the surgeon`s existing skills, provides direct action-task correspondence, eliminates explicit modes for separate tools, facilitates natural two-handed interaction, and provides tactile and kinesthetic feedback for the user. Our informal evaluation sessions have shown that with a cursory introduction, neurosurgeons who have never seen the interface can understand and use it without training.